2018
DOI: 10.1038/nrg.2017.108
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness analyses of genetic and genomic diagnostic tests

Abstract: Developments in next-generation sequencing technologies have driven the clinical application of diagnostic tests that interrogate the whole genome, which offer the chance to diagnose rare inherited diseases or inform the targeting of therapies. New genomic diagnostic tests compete with traditional approaches to diagnosis, including the genetic testing of single genes and other clinical strategies, for finite health-care budgets. In this context, decision analytic model-based cost-effectiveness analysis is a us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 74 publications
0
102
0
2
Order By: Relevance
“…We are living in an exciting time of major technological advancements in genetics. The next‐generation sequencing (NGS) technology has rapidly evolved since the time of human genome project in 2003 with a declining cost of ~US$10 million in 2007 to $1500 in 2015 . NGS commonly refers to a technology of massively parallel sequencing of small fragments of DNA or RNA in a relatively short time .…”
Section: Implications For Orthodonticsmentioning
confidence: 99%
“…We are living in an exciting time of major technological advancements in genetics. The next‐generation sequencing (NGS) technology has rapidly evolved since the time of human genome project in 2003 with a declining cost of ~US$10 million in 2007 to $1500 in 2015 . NGS commonly refers to a technology of massively parallel sequencing of small fragments of DNA or RNA in a relatively short time .…”
Section: Implications For Orthodonticsmentioning
confidence: 99%
“…For example, clinical decisions may be challenging if the cut point for a continuous test result is disputed or if multiple treatment strategies are possible following a particular test result. In practice, therefore, the imperfect implementation [61] of a testing strategy, through clinicians’ prescribing behavior, may contribute to overestimating the net health gain obtained from a precision medicine [20]. …”
Section: The Economic Case: In Practicementioning
confidence: 99%
“…An extensive literature of published economic evaluations of health technologies for precision medicine is developing [1119] and, in 2016, some 45 systematic reviews on this topic were identified [20]. The specific challenges in designing and conducting economic evaluations of precision medicine have also been described [2127].…”
Section: Introductionmentioning
confidence: 99%
“…We may view each gene as a vector with one component corresponding to each residue mutation in the gene, together with a weight for each component that is given by (1). Therefore, we can find the overlap score measure with the rf − igf weight of each term in g, for a query q;…”
Section: Genome-wide and Disease-specific Applicationmentioning
confidence: 99%
“…Costs associated with genomic investigations continue to reduce [1] while the richness of data generated increases. Globally, the adoption of wide scale genome sequencing implies that all new-born infants may receive screening for pathogenic genetic variants in an asymptomatic stage, pre-emptively [2].…”
Section: Introductionmentioning
confidence: 99%